긍정심리학의 생물학적 배경 - 강은호(Eun-Ho Kang); 박주언(Joo-Eon Park); 채정호(Jeong-Ho Chae); 박영민(Young Min Park); 최삼욱(Sam-Wook Choi) (Seuteureseu yeon-gu (Online), 2008)
Most modern researches have focused on the underlying biological mechanisms as the basis of various psychopathology such as psychosis, depression, anxiety, etc. However, little is known about the biological basis of positive psychology. Recent developments in biological and neuroscientific techniques enable us to speculate that there are also biological basis in the field of positive psychology. The author introduces some important researches on the biological basis of positive psychology. (Korean J Str Res 2008;16:281∼285) KCI Citation Count: 1